2018
DOI: 10.1111/jth.14310
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic abnormalities in patients with Ehlers–Danlos syndrome

Abstract: Martinelli I. Hemostatic abnormalities in patients with Ehlers-Danlos syndrome. J Thromb Haemost 2018; 16: 2425-31. Essentials • Ehlers-Danlos Syndrome (EDS) is a rare heterogeneous group of inherited collagen disorders. • A cohort of EDS patients was investigated for bleeding tendency and hemostatic abnormalities. • EDS is associated with an increased risk of bleeding. • EDS patients have platelet function abnormalities, whose severity correlates with bleeding risk. Summary. Background: Ehlers-Danlos syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…A recent case‐control study revealed that the prevalence of symptomatic joint hypermobility/suspected collagen disorders in patients referred to a bleeding disorder clinic was higher than in the age‐ and gender‐matched controls . Conversely, most hypermobile patients report symptoms of easy bruising and many have objective signs of abnormal bleeding . This suggests the contribution of abnormal collagen, which is reflected in symptomatic joint hypermobility, to the expression of bleeding tendency.…”
Section: Bleeding and Bruising In The Hypermobile Patientmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent case‐control study revealed that the prevalence of symptomatic joint hypermobility/suspected collagen disorders in patients referred to a bleeding disorder clinic was higher than in the age‐ and gender‐matched controls . Conversely, most hypermobile patients report symptoms of easy bruising and many have objective signs of abnormal bleeding . This suggests the contribution of abnormal collagen, which is reflected in symptomatic joint hypermobility, to the expression of bleeding tendency.…”
Section: Bleeding and Bruising In The Hypermobile Patientmentioning
confidence: 99%
“…More recently, it has been shown that patients with vascular EDS have a platelet dysfunction, although this was studied only in a small cohort of patients and will need to be tested in a larger group of patients . A recent comprehensive study described significant platelet function abnormalities in patients with EDS and the absence of any consistent coagulation defect including thrombin generation …”
Section: Bleeding and Bruising In The Hypermobile Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…| 251 bioprosthetic valve was chosen by the patient and to avoid the systemic anticoagulation. 6 Moreover, in the case of valve structural degeneration, usually within 12 to 20 years, the valve in valve transcatheter aortic valve implantation would be a safe and feasible option. 7 Likewise, we felt that due to the severity of the PE, the compression of the right ventricle combined with the fragility of tissues and the previous cosmetic intervention plus the desire of the patient for a permanent solution to his problem necessitated sternal bar support as a less invasive approach.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is interesting to note that the Ehlers-Danlos syndrome, another connective tissue disease which may be accompanied by aortic dilatation, can be associated with platelet dysfunction [373][374][375]. Platelet dysfunction could be found in Marfan patients as well, analyzed by the Multiplate and PFA 100 tests [353].…”
Section: Platelet Dysfunctionmentioning
confidence: 99%